Pengaruh Penggunaan BRImo melalui QRIS terhadap Pengelolaan Keuangan Mahasiswa Universitas Bengkulu - Selfa Andreyani; Anggun Tri Lestari; Lendea Verandani; Khairunnisa Rizki A; Febriano Duta Rifanka (INDO PUBLISHING, 2026)
The development of digital technology has made financial transactions easier for the public, including through the BRImo application with the QRIS feature. This feature allows users to make payments quickly and practically without using cash. This study aims to determine the effect of using BRImo through QRIS on the financial management of students at the University of Bengkulu. This research uses a quantitative method by collecting data through questionnaires distributed to students who use BRImo. The results show that the use of BRImo through QRIS has an influence on how students manage their finances, especially in making transactions and organizing their expenses more practically